2020
DOI: 10.1093/jamiaopen/ooaa006
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for early detection of sepsis: an internal and temporal validation study

Abstract: Objective Determine if deep learning detects sepsis earlier and more accurately than other models. To evaluate model performance using implementation-oriented metrics that simulate clinical practice. Materials and Methods We trained internally and temporally validated a deep learning model (multi-output Gaussian process and recurrent neural network [MGP–RNN]) to detect sepsis using encounters from adult hospitalized patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Adding a human intermediary has its own challenges, such as interrupting busy ED workflows and additional delays with remote monitoring. For example, despite the model’s high predictive value within the first hour of ED presentation [ 44 ], nurses sometimes waited for more clinical information to populate in the medical record before calling physicians about patients flagged as being at high-risk for sepsis. In future iterations of the program, these human-made delays need to be anticipated and addressed through training or workflow design to ensure patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Adding a human intermediary has its own challenges, such as interrupting busy ED workflows and additional delays with remote monitoring. For example, despite the model’s high predictive value within the first hour of ED presentation [ 44 ], nurses sometimes waited for more clinical information to populate in the medical record before calling physicians about patients flagged as being at high-risk for sepsis. In future iterations of the program, these human-made delays need to be anticipated and addressed through training or workflow design to ensure patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) Sepsis3.0 Mortality prediction of sepsis MIMIC III v1.4 Remove the variables with more than 20% observations missing + multiple imputation method NR NR NR Kong et al. (2020) Sepsis3.0 Mortality prediction of sepsis MIMIC III Remove the patients with more than 30% predictor variable missing + Replace by mean value NR NR NR Bedoya et al. (2020) SIRS + infection + end organ failure Early detection of sepsis ED of a quaternary academic hospital NR NR NR NR van Doorn et al.…”
Section: Resultsmentioning
confidence: 99%
“…Bedoya et al fixed the number of alerts allowed per hour and reported the number of sepsis cases identified early per day to reflect the need to limit the number of alerts given to front-line clinicians 23 . To simulate a real-time scenario, evaluation metrics were calculated using the maximum score within windows ranging in size from 1 to 12 h. This kind of evaluation allowed the authors to plot the average cases detected early against the average alarms fired, which visualizes the threshold trade-off in a new way.…”
Section: Discussionmentioning
confidence: 99%